VALIDITY OF LAND GRANTS IN THE CONSTRUCTION OF DRINKING WATER FACILITIES MADE UNDER HAND IN THE DRINKING WATER SUPPLY PROGRAM AND COMMUNITY BASED SANITATION - Clarissa, Grace Agnes (Zhata Institut, 2024)
The implementation of land grants for the construction of drinking water facilities which are made privately and what is the validity of the private grant agreements that occur in the implementation of private grants in the Pamsimas program. The purpose of this research is to explain the implementation of grants that occur in the field in the Pamsimas program, as well as know the legal validity of land grants made privately. With the Pamsimas program implemented by the government which aims to provide clean water facilities for the community, land is needed to support construction development, so the community must contribute in the form of donating their land to the village government as a condition that must be met for the implementation of the Pamsimas program. This research was conducted in 3 provinces, namely Riau Province, Bangka Belitung Province, and Jambi Province. The problem in this research is the implementation of grant giving by village communities in the Pamsimas program by making grant statements privately, which means it is done without a PPAT deed being made and the land grants given on average do not have land certificates or have not been registered with the National Land Agency registrar. , and how valid it is. This happens due to a lack of legal understanding regarding land grant procedures according to the law and it has become a habit for village communities to make land grants privately without doing it before the PPAT. Another cause is the lack of costs to make a PPAT deed. The solution to this problem is by providing outreach to the community to understand what a grant is and registering the land one year before the development is carried out. Apart from that, the validity of the grant letter being executed is invalid because Government Regulation No. 24 of 1997 concerning land registration states that every grant of land and buildings must be made with a Deed from the Official Land Deed Maker (PPAT). If a grant in the form of land is not made by a notary, it will not have legal force.